2017
DOI: 10.1007/s00894-017-3285-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the impact of surfactant structure on interfacial tension: a molecular dynamics study

Abstract: The effect of sodium branched-alkylbenzene sulfonates on the NaCl solution/oil interface was studied via classical molecular dynamics simulation. The interfacial properties were found to depend on the surfactant concentration and to change dramatically when the concentration exceeded a critical value, the simulated limit area (A ). When A is not close to the theoretical saturated adsorption area (A ), the surfactant cannot produce ultralow interfacial tension (IFT). When A is equal or almost equal to A , the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The interfacial thickness of the individual HBS7 system was 1.43 nm, which was in good agreement with that of the n ‐nonane/branched pentadecylbenzene sulfonate/water system, 1.41 nm (Liu et al, 2017). The distance between the center position of the distribution peak of the SFT head group and water phase for the SFT individual system was 0.91 nm.…”
Section: Resultssupporting
confidence: 77%
“…The interfacial thickness of the individual HBS7 system was 1.43 nm, which was in good agreement with that of the n ‐nonane/branched pentadecylbenzene sulfonate/water system, 1.41 nm (Liu et al, 2017). The distance between the center position of the distribution peak of the SFT head group and water phase for the SFT individual system was 0.91 nm.…”
Section: Resultssupporting
confidence: 77%
“…The present work is limited to the investigation of vapour-liquid interfaces of binary mixtures of molecular fluids. Related work on electrolyte solutions and ionic liquids [2,[37][38][39][40][41][42][43], on the behaviour of surfactants at interfaces [44][45][46][47][48][49], as well as on the enrichment of components at liquid-liquid interfaces [27,31,33,[50][51][52][53][54] is not covered. Since theoretical methods for the prediction of component density profiles, namely molecular simulation, DGT, and DFT have been reviewed in detail elsewhere [55][56][57][58][59] their description is not subject of the present paper.…”
mentioning
confidence: 99%
“…It can also be found that the heights of the two peaks of 2-C16 are similar regardless of whether it is near the hydroxyl group or the ketone group, and the second peak is higher than the other three surfactants. It is speculated that this is because the steric hindrance effect of 2-C16 in the rigid short-chain branch at m = 2 causes it to be more inclined to stay away from the coal surface [3,19,40]. Furthermore, according to existing research [9], the shorter the alkane chain, the lower the viscosity, the weaker the intermolecular force is, and the easier it is to produce a translation, rotation, and deformation when subjected to other forces.…”
Section: Relative Concentration Distributionmentioning
confidence: 99%
“…This is due to the fact that as the sulfonate group moves to the middle of the backbone, the short-chain branch becomes longer, resulting in a size change of the hydrophobic part of the surfactant molecule. According to the literature [3,[45][46][47], when the size of the hydrophobic group and the hydrophilic group is similar, the surfactant molecule almost covers the entire interface, and the CSA is the largest at this time. It shows that the size of the hydrophobic part composed of the short-chain branch composed of 4 carbon atoms and the long-chain branch composed of 12 carbon atoms in 4-C16 is similar to the size of the hydrophilic group of benzenesulfonic acid, which leads to the largest CSA with anthracite.…”
Section: Contact Surface Areamentioning
confidence: 99%
See 1 more Smart Citation